Comparison between holmium laser and cold knife direct vision internal urethrotomy for treatment of urethral stricture - Kegham, Hrair Haik; Khudhur, Ahmed Imad; Ameen, Ali Abdulqader (International Surgery Journal, 2017)
Background: Urethral stricture (US) is one of the most difficult urological problems to cure adequately and is known to mankind since ages as it had been documented in ancient literature of the Hindus, Egyptians and Greeks and Islamic cultures. The aim of this study is to compare between Ho: YAG (holmium laser) and cold knife direct vision internal urethrotomy for the treatment of short segment urethral stricture regarding efficacy of treatment, operative time and complications. Methods: A prospective study was conducted on a total of 38 male patients with definitive diagnosis of urethral stricture attending the urological outpatient clinic of Al Karama teaching hospital from September 2013 to May 2015. All patients involved agreed to participate in this study. Results: In this study, total number of patients 31 mean age (43.94±11.70). In the holmium group, 16 patients with mean age (42.06±10.43), in cold knife group, 15 patients with mean age (45.93±12.99). Regarding causes of urethral stricture, from total 31 patients 8 patients had infection, 11 traumatic, 10 iatrogenic and 2 unknown (idiopathic), in the holmium 4 patients had infection, 6 traumatic, 4 iatrogenic and one unknown. In cold knife group 4 patients had infection, 5 traumatic, 6 iatrogenic and one was unknown. In holmium group, 12 patients had strictures in anterior segment, 4 patients had it in posterior segment urethra, in cold knife group, there were 10 patients with strictures in anterior segment and 5 patients in posterior segment urethra. The peak flow rates were compared between the two groups pre‑ and post‑operatively at 15 days, 3 months, and 6 months. At day 15 and 3 months, the difference between the means of peak flow rates (PFR) was not statistically significant and was comparable. At 6 months interval, the difference between mean of PFR for holmium and cold knife group was statistically highly significant. Conclusions: Urethral stricture is a disease affecting middle-aged men. Both cold knife and laser urethrotomy are effective method for treatment of short segment urethral stricture. The change in Q-max was observed to be greater with cold knife than with laser with statistical significance at 6 months. Operative time was shorter in cold knife group.